Pharmacodynamics of a Simulated Single 1,200-Milligram Dose of Oritavancin in an In Vitro Pharmacokinetic/Pharmacodynamic Model of Methicillin-Resistant Staphylococcus aureus Infection - Belley, Adam (American Society for Microbiology, 2013)
The safety and efficacy of a single 1,200-mg dose of the lipoglycopeptide oritavancin are currently being investigated in two global phase 3 studies of acute bacterial skin and skin structure infections. In this study, an in vitro pharmacokinetic/pharmacodynamic model was established to compare the free-drug pharmacodynamics associated with a single 1,200-mg dose of oritavancin to once-daily dosing with daptomycin at 6 mg/kg of body weight and twice-daily dosing with vancomycin at 1,000 mg against three methicillin-resistant Staphylococcus aureus (MRSA) strains over 72 h. The area under the bacterial-kill curve (AUBKC) was used to assess the antibacterial effect of each dosing regimen at 24 h (AUBKC(0-24)), 48 h (AUBKC(0-48)), and 72 h (AUBKC(0-72)). The rapid bactericidal activities of oritavancin and daptomycin contributed to lower AUBKC(0-24)s for the three MRSA strains than with vancomycin (P < 0.05, as determined by analysis of variance [ANOVA]). Oritavancin exposure also resulted in a lower AUBKC(0-48) and AUBKC(0-72) against one MRSA strain and a lower AUBKC(0-48) for another strain than did vancomycin exposure (P < 0.05). Furthermore, daptomycin exposure resulted in a lower AUBKC(0-48) and AUBKC(0-72) for one of the MRSA isolates than did vancomycin exposure (P < 0.05). Lower AUBKC(0-24)s for two of the MRSA strains (P < 0.05) were obtained with oritavancin exposure than with daptomycin. Thus, the antibacterial effect from the single-dose regimen of oritavancin is as effective as that from either once-daily dosing with daptomycin or twice-daily dosing with vancomycin against the MRSA isolates tested in an in vitro pharmacokinetic/pharmacodynamic model over 72 h. These results provide further justification to assess the single 1,200-mg dose of oritavancin for treatment of acute bacterial skin and skin structure infections.